2018
DOI: 10.1186/s12961-018-0302-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between health research output and burden of disease in Arab countries: evidence from Palestine

Abstract: BackgroundResearch conducted on conditions responsible for the greatest disease burden should be given the highest priority, particularly in resource-limited settings. The present study aimed to assess the research output in relation to disease burden in Palestine and to identify the conditions which are under- or over-investigated, if any.MethodsWe searched PubMed and Scopus for reports of original research relevant to human health or healthcare authored by researchers affiliated with Palestinian institutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
1
23
0
1
Order By: Relevance
“…Similar observations were emphasised in a recent scoping review of NCD research in the region spanning the years 2000 until 2013, noting higher publication rates and the most rapid increases overtime in high-income countries [9]. With the exception of Iran, our findings of limited research productivity of systematic reviews on NCDs in the region (on average 2 publications per country) and of reviews evaluating interventions for the same NCD condition or in a single population align with the larger body of literature indicating a relative scarcity of high-evidence research [9,17]. Reasons for the relatively lower quantity and quality of scientific productivity in the EMR include deficient research funding [27], instability of countries during conflicts [28,29], poor research infrastructure, inadequate human resources and capacity, and difficulty in accessing biomedical databases and high-quality journals [30].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Similar observations were emphasised in a recent scoping review of NCD research in the region spanning the years 2000 until 2013, noting higher publication rates and the most rapid increases overtime in high-income countries [9]. With the exception of Iran, our findings of limited research productivity of systematic reviews on NCDs in the region (on average 2 publications per country) and of reviews evaluating interventions for the same NCD condition or in a single population align with the larger body of literature indicating a relative scarcity of high-evidence research [9,17]. Reasons for the relatively lower quantity and quality of scientific productivity in the EMR include deficient research funding [27], instability of countries during conflicts [28,29], poor research infrastructure, inadequate human resources and capacity, and difficulty in accessing biomedical databases and high-quality journals [30].…”
Section: Discussionsupporting
confidence: 66%
“…These have scarcely begun to be explored in the global literature, with one study relying solely on the Cochrane database of systematic reviews [13] and another covering a single NCD condition, diabetes [14]. Previous NCD reviews in the region have either had broader scope of inclusion criteria incorporating studies of various methodologies including primary studies [9], or were focused on a distinct theme in NCD research (e.g cost analyses or genetics in NCD research) [15,16] or a single country [17]. However, no previous study has appraised NCD-related evidence generated from exclusively systematic reviews.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that diseases that impose a high health and economic burden on society should ideally receive more attention from both funders and the research community [1–3]. However, this has not been the case for most low‐ and middle‐income countries (LMIC).…”
Section: Introductionmentioning
confidence: 99%
“…Research output has been used as a proxy indicator of research prioritisation [9]. The analysis of the balance between the burden of disease and its research output is likely to reveal health conditions that may be relatively under‐ or over‐studied [1]. Highlighting a possible disparity is therefore critical in guiding stakeholders and policymakers on the allocation of limited health research resources.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is estimated to have only 1.1% of global research resources in 2013 (81). A study on health research outputs in Palestine indicates the presence of a mismatch between the health burden of certain disease conditions and the number of published research reports on those diseases (82). Such discordance between research output and disease burden was also demonstrated in a study that covered research on noncommunicable diseases in seven Arab countries (68).…”
Section: Géographie De La Recherche En Biomédecine Et En Santé Dans Lmentioning
confidence: 99%